(untitled) (Acta Scientiarum. Health Sciences, 2012)
The process of aging results in several changes in the organisms, thus, is necessary to search for ways to mitigate the negative effects of this involution process, for this, knowing that the strength improvement represents a greater availability for everyday activities, this study searched at strength training, evidence of possible improvements in variables related to elderly autonomy. Before and after 12 weeks of training, we performed a pre and post-assessment respectively, in which were measured anthropometric variables as body weight, height, body mass index, waist and hip circumference, waist-hip ratio and fat. We also performed a strength test with hand-held and lower-limb dynamometers, besides functional capacity tests as climbing stairs and self-perception performance in activities of daily living. The sample consisted of 12 elderly females without any type of strength training. The results showed a significant improvement in strength and functional capacity, there was also significant reduction of fat, and increase of lean body mass. Concluding, elderly people can enjoy the benefits provided by strength training, especially in autonomy perspective.